High-Yield Birth-Cohort Hepatitis C Virus Screening and Linkage to Care Among Underserved African Americans, Atlanta, Georgia, 2012–2013 - Miller, Lesley S. (Public Health Rep, 2016)
OBJECTIVE: Hepatitis C virus (HCV) infection disproportionately affects certain populations, including those born between 1945 and 1965 (i.e., baby boomers) and African Americans. As part of the Hepatitis Testing and Linkage to Care initiative, which promoted hepatitis B and hepatitis C screening, posttest counseling, and linkage to care at 34 U.S. sites, we conducted routine HCV screening to identify previously undiagnosed, primarily African American baby boomers with chronic hepatitis C infection and link them to care. METHODS: We launched the Internal Medicine Trainees Identifying and Linking to Treatment for Hepatitis C (TILT-C) initiative at the Grady Memorial Hospital Primary Care Center and Grady Liver Clinic in Atlanta, Georgia, in October 2012, and present results from the first year. TILT-C faculty implemented an electronic medical record prompt and conducted educational sessions to boost HCV screening. A project coordinator tracked testing outcomes and linked HCV-positive patients to care. RESULTS: Of 2,894 patients tested for anti-HCV, 201 (6.9%) tested positive. Men had a significantly higher (p<0.001) prevalence of HCV infection than women, with 106 of 1,091 (9.7%) men compared with 95 of 1,803 (5.3%) women testing anti-HCV positive. A total of 174 of 201 (86.6%) anti-HCV-positive patients received HCV ribonucleic acid (RNA) testing. Of 124 patients with a positive HCV RNA test, 122 were referred to care and 120 attended the first appointment. CONCLUSION: The TILT-C screening program was feasible and effective in detecting previously undiagnosed HCV infection and linking patients to care. The unexpectedly high prevalence of HCV infection in this primarily African American, baby boomer population underscores the need for aggressive HCV screening efforts in similar populations.